Protocolo assistencial para atendimento às gestantes com toxoplasmose - Oliveira, Rosa Maria Prado de (2025)
Introduction: Congenital toxoplasmosis is vertically transmitted and presents diagnostic challenges due to frequently nonspecific symptoms. Between 2019 and 2024, national data indicated an increase in cases, highlighting the importance of early diagnosis and treatment to prevent serious complications. This study proposes a care protocol based on a rapid review and existing guidelines, focused on the management of pregnant women with toxoplasmosis. The approach aims to standardize care, reduce errors, and promote better outcomes through evidence-based practices adaptable to other services. Objective: To create a care protocol for the management of pregnant women with toxoplasmosis, based on scientific evidence. Methodology: This study consists of three complementary stages designed to answer the research question. The first stage involved a rapid systematic review, combined with a search for care protocols for the management of toxoplasmosis using the Google and Fala.BR platforms. The second stage addressed the identification of barriers and limitations in protocol development, based on critical analysis of the selected studies and institutional documents. The third stage involved the development of a systematic and interdisciplinary care protocol for pregnant women with toxoplasmosis, grounded in the evidence gathered. Results: Initially, 5,726 articles were retrieved. After completing all selection steps, 31 articles were included, categorized by title, author/year/country, study design, technology used, comparison methods, results, limitations, study context, and the presence or absence of clinical flowcharts. Regarding institutional protocols, eight were found on the Google platform and five on Fala.BR. In the second stage, barriers to protocol creation were identified, including the lack of clinical flowcharts, unstandardized care practices, and limited access to qualified technical materials. In the third stage, a systematic and interdisciplinary care protocol was developed, encompassing the management of pregnant women with toxoplasmosis. Conclusion: This study supported the development of an evidence-based care protocol for the management of pregnant women with toxoplasmosis. The technical and documentary analysis revealed challenges such as the lack of clinical flowcharts, inconsistencies in care practices, and difficulties accessing technical materials. As a facilitating factor, the availability of numerous scientific articles on the topic stands out. The consolidation of the protocol will depend on team adherence and adaptation to local realities. This experience may guide similar initiatives in other settings.